ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS DALAM MATERI BARISAN DAN DERET ARITMATIKA DITINJAU DARI GAYA BELAJAR SISWA DIKELAS 8 - Laras Ayu Lestari (LPD IKIP PGRI Pontianak, 2023)
Abstract: This study aims to describe the ability of mathematical representation in the material for sequences and series in terms of the learning styles of students in class 8 MTS AL-MA'ARIF Pontianak Academic Year 2022/2023. This research uses descriptive research with a qualitative approach. The method used is a learning style questionnaire, mathematical representation test, and interviews. The subjects in this study were 6 students consisting of 2 visual learning style students, 2 auditory learning style students, 2 kinesthetic learning style students. The results of this study indicate that (1) the mathematical representation abilities of subjects who have a visual learning style are less able to solve problems (2) the mathematical representation abilities of subjects who have an auditory learning style are almost able to solve all questions correctly (3) the mathematical representation abilities of subjects who have kinesthetic learning style has not been able to solve all the problems.Â Â